Affluent Prognosis of Hepatitis C after Interferon Therapy and Disease Epidemiology in Rawalpindi, Pakistan: Affluent Prognosis of Hepatitis C after Interferon Therapy and Disease Epidemiology in Rawalpindi - Habib, Rukhshanda; Saeed, Asma; Khan, Barkat Ali (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2017)
Hepatitis C (HCV) affects around 3% of the world population and, thus, remains a global threat. Globally, Pakistan is at second place with regard to incidence of HCV, as 4.5-8.0% of its population is infected with HCV. Diagnosis of hepatitis C patients after interferon therapy is poorly demarcated till today. Aim of the present study was to evaluate effect of interferon, ribavirin combined therapy on survival of hepatitis C patients. This study was conducted in District Head Quarter (D.H.Q.) Teaching Hospital, Rawalpindi, Pakistan to diagnose hepatitis C after interferon combined therapy of the patients. The study span was one year and included 237 chronic hepatitis C patients. Hepatitis C diagnosis was made by polymerase chain reaction (PCR). Treatment response was evaluated by medical reports. All patients were educated for the follow-up; however, only 143 (i.e., 60%) out of the total 237 patients completed the 6-month interferon combined therapy; the remaining 94 patients (i.e., 40% of total) discontinued the treatment. The treated patients included 59 (i.e., 41%) of total 143 malesand 84(i.e., 59%) total females. Among male patients,45 (i.e., 76%)out of total 59exhibited treatment success, while 14(i.e., 24%) exhibited treatment failure. In case of female patients, 68(i.e., 81%) out of total 84 revealed treatment success and 16 (19%) revealed treatment failure. Treatment success was attributed to multiple factors, while failure occurred because of non-adherence to the treatment protocol, unawareness of the complications and/or concurrent infection with HIV.